Симетрійний аналіз та точні розв'язки одного класу (1 + 3)-вимірних крайових задач типу Стефана - Коваленко, С.С. (Український математичний журнал, 2011)
Проведена групповая классификация одного класса (1 + 3)-мерных нелинейных краевых задач типа Стефана, которые моделируют процессы плавления и испарения металлов. Полученные результаты применены для построения точного решения одной краевой задачи из исследуемого класса. We present the group classification of one class of (1 + 3)-dimensional nonlinear boundary-value problems of the Stefan type that model the processes of melting and evaporation of metals. The results obtained are used for the construction of the exact solution of one boundary-value problem from the class under study.